Improving MACD technical analysis by optimizing parameters and modifying trading rules: Evidence from the Japanese Nikkei 225 futures market - Byung-Kook Kang (Journal of Risk and Financial Management, 2021)
Much research has examined performance or market efficiency by using the moving average convergence divergence (MACD) technical analysis tool. However, most tests fail to verify efficiency with the traditional parameter settings of 12, 26, and 9 days. This study confirms that applying the traditional model to Japan's Nikkei 225 futures prices produces negative performance over the period of 2011-2019. Yet, it also finds that the MACD tool can earn significant positive returns when it uses optimized parameter values. This suggests that the Japanese market is not weak-form efficient in the sense that futures prices do not reflect all public information. Hence, the three parameters values of the MACD tool should be optimized for each market and this should take precedence over finding other strategies to reduce false trade signals. This study also tests which models are able to improve profitability by applying additional criteria to avoid false trade signals. From simulations using 19,456 different MACD models, we find that the number of models with improved performance resulting from these strategies is far greater for models with optimized parameter values than for models with non-optimized values. This approach has not been discussed in the existing literature.
Keywords: 330; MACD; technical analysis; trading simulation; buy-and-hold strategy; market efficiency; Nikkei 225 futures